Synthesis, Characterization and Spectroscopic Studies of A Novel 2-[(E)-[(2,4-dichlorophenyl)imino]methyl]phenol Schiff Base and Its Metal Complexes - Eman Turky Shamkhy; Isam Hussain T. Al-Karkhi (E-Journal of Chemistry)
A novel Schiff base 2-{(E)-[(2,4-dichlorophenyl)imino]methyl}phenol (LB) was synthesized from the condensation reaction of 2,4-dichloroaniline with salicyladehyde in [1:1] ratio in the presence of glacial acetic acid as catalyst. Complexation reaction of this Schiff base with copper (II), cobalt (II) as nitrate salts and with Rhodium (III) as chloride salt to produce three coordinate metal complexes, with a Schiff base: Metal ion ratio of 2:1. These compounds have been characterized by a variety of physico-chemical and spectroscopic techniques. The ligand and its metal complexes were expected to show an interesting bioactivity and cytotoxicity.